Predicting the final time in slalom based on the time of the first and second race - Mijanovic, M.; Matkovic, B. (SportLogia, 2011)
Prediction of final race time in slalom based on the time achieved in first and second race is a paper with a purpose and a primary goal to address the attention to relevant factors that determine final result in alpine skiing, and all that based on exact indicators gained under exact and strictly controlled rules of FIS. The mentioned example is about slalom discipline. Due to the fact that the result is a primary goal, the asked question is: Does the final result depend more on time achieved in first or in second race? Precise and direct answer is given in the conclusion of the paper. The conclusion is formed on the basis of precise results gained in the World Cup race. The race took place in Zagreb, Sljeme, 2010. Gained results indicate a conclusion that a total time in slalom is in a high positive correlation with achieved time in first race. Multiple correlation coefficient and multiple determination coefficient of first and second race compared to total time is high and statistically significant in example R = .67, R2 = .45, p </= .001. Standardized predictive values of Beta in Table 7 give the right to conclude that achieved time in first race is more significant, or have more influence on the final result comparing to the time achieved in second race, in example Beta1 = .55, and Beta2 = .40. Assuming that general conditions of competitions are approximately same, the reasons of bigger influence of first than the second race should be looked for in tactics of coaches and competitors. The reasons for changing of tactics for the first and for the second race are determined by the FIS rules. Among other things, rules state that right for participating in second race have only first 30 participants from the first race. The natural conclusion is that the first race, or ride, is without any calculations and by principle "all or nothing". The tactic of second race is significantly different. The race must successfully end, even with risk of insignificant improve, or even failure. Of course, the weather can influence on better or worse result. In accordance with the law of possibility the influence of weather is evened, or annulled.